The acute effects of L-arginine on hormonal and metabolic responses during submaximal exercise in trained cyclists - Forbes, S. C.; Harber, V. J.; Bell, G. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
L-arginine may enhance endurance performance mediated by two primary mechanisms including enhanced secretion of endogenous growth hormone (GH) and as a precursor of nitric oxide (NO); however, research in trained participants has been equivocal. The purpose was to investigate the effect of acute L-arginine ingestion on the hormonal and metabolic response during submaximal exercise in trained cyclists. Fifteen aerobically trained men (age: 28 ± 5 y; body mass: 77.4 ± 9.5 kg; height: 180.9 ± 7.9 cm; VO2max: 59.6 ± 5.9 ml/kg·min) participated in a randomized, double-blind, crossover study. Subjects consumed L-arginine (ARG; 0.075 g·kg-1 body mass) or a placebo (PLA) before performing an acute bout of submaximal exercise (60 min at 80% of power output achieved at ventilatory threshold). The ARG condition significantly increased plasma L-arginine concentrations (~146%), while no change was detected in the PLA condition. There were no differences between conditions for GH, nonesterified fatty acids (NEFA), lactate, glucose, VO2, VCO2, RER, CHO oxidation, and NOx. There was reduced fat oxidation at the start of exercise (ARG: 0.36 ± 0.25 vs. PLA: 0.42 ± 0.23 g/min, p < .05) and an elevated plasma glycerol concentrations at the 45-min time point (ARG: 340.3 vs. PLA: 288.5 mol/L, p < .05) after L-arginine consumption. In conclusion, the acute ingestion of L-arginine did not alter any hormonal, metabolic, or cardio-respiratory responses during submaximal exercise except for a small but significant increase in glycerol at the 45-min time point and a reduction in fat oxidation at the start of exercise.